Cinnamon Extract Effect on Osteoblast Activity in Diabetic Wistar Rats - Andiwijaya, Fahrin Ramadan; Prihatanto, Fundhy Sinar Ikrar; Susanto, Hermawan (BALI MEDICAL JOURNAL, 2016)
Background: Diabetes is clinically known to cause prolongation to bone fracture healing. This research aims to find the effect of cinnamon in the process of bone remodeling, and changes in the activity of osteoblast cells in diabetic bone after giving cinnamon as a supplement in diabetic rats. Method: The design employed was experimental with randomized post-test group design research. A total of 24 Wistar Rats was randomly divided into four groups, which consist of normal without treatment, normal with treatment, diabetic without treatment and diabetic with treatment. Treatment of 300 mg/kg cinnamon extract was given per orally. Upon euthanizing the samples, femur samples were taken and processed to histopathological slides. All slides were analyzed under light microscopes to find the osteoblast cells. The Kruskal-Wallis method was used to test the results; due to the population of sample was not normally distributed. Results: The osteoblast cells found were scored in mean ranks. The normal group mean rank 12.25, normal with treatment group 12.17, diabetic without treatment group 8.58, and diabetic with treatment group 17.00. Asymptotic significance was 0.195. Conclusion: This research concludes that there is no significant increase in osteoblast activity in diabetic Wistar rats after the administration of 300 mg/kg cinnamon extract.
Keywords: Diabetes, Wistar Rats, Cinnamon, Histopathological, Osteoblast Cells.